A numerical method for manoeuvring simulation in regular waves. (15th December 2018) - Chillcce, Guillermo; el Moctar, Ould
Abstract: A numerical method to simulate ship manoeuvring in waves is presented. The method solves the six degrees of freedom (DoF) nonlinear equations of motion described in an inertial coordinate system. It was assumed that calm water manoeuvring and wave induced forces do not interact. Thus, those forces were computed separately. Calm water forces were calculated using hydrodynamic coefficients obtained by planar motion mechanism (PMM) tests using Reynolds-Averaged Navier Stokes (RANS) equations. Only wave-induced second order forces were considered, which were calculated using a 3D RANKINE source based boundary element method. The simulation method developed was applied for the 14, 000 TEU containership Duisburg Test Case (DTC), for which experimental data for manoeuvring motions in calm water and waves are available. The computed and measured manoeuvring motions in calm water and in waves correlate fairly. Highlights: A new numerical approach to simulate ship manoeuvring in regular waves based on inertial coordinate system. The method is valid for 6DoF and it contains all motion nonlinearities. The equations of motion only assumption is that the ship is rigid. Second order wave force and moment depend on velocity and relative heading between ship and wave. Ship drift direction is captured by using the second order wave forces.